2021
DOI: 10.1002/adom.202002108
|View full text |Cite
|
Sign up to set email alerts
|

Efficient Semi‐Transparent Organic Solar Cells with High Color Rendering Index Enabled by Self‐Assembled and Knitted AgNPs/MWCNTs Transparent Top Electrode via Solution Process

Abstract: conversion efficiency (PCE) has already exceeded 16% enabled by advanced photovoltaic materials. [3][4][5][6] Although opaque OSCs exhibit high efficiency, their usage is limited because they demand dedicated space and additional installation work on the roof, like traditional silicon solar cells. Therefore, the transparent property of OSCs was exploited for semi-transparent photovoltaic modules to extend their application in power-generating windows for buildings and automobiles. To fabricate efficient semi-t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 69 publications
1
16
0
Order By: Relevance
“…This ST-OSC achieved a PCE of 7% with a high AVT of 36% and a colour rendering index of 90. 228 We further improved the PCE to 13.19% with AVT of 24.56% by using a ternary blend of PBDB-TF, Y6 and our in-house designed BDC-4F-C8. 229 Hou et al reported PBDB-T donor with IEIC-4Cl.…”
Section: Device Architecture Engineering For the Oscsmentioning
confidence: 99%
“…This ST-OSC achieved a PCE of 7% with a high AVT of 36% and a colour rendering index of 90. 228 We further improved the PCE to 13.19% with AVT of 24.56% by using a ternary blend of PBDB-TF, Y6 and our in-house designed BDC-4F-C8. 229 Hou et al reported PBDB-T donor with IEIC-4Cl.…”
Section: Device Architecture Engineering For the Oscsmentioning
confidence: 99%
“…Interestingly, the MWCNT-based devices managed to retain above 80% of their original PCE after storage for 10 days under environmental conditions, and also managed to maintain their initial PCE, above 90%, after 100 bending cycles, demonstrating their superior long-term environmental stability and excellent flexibility. Recently, a relatively high PCE of 7% has been obtained after introducing Ag nanoparticles (NPs) into MWCNT-based anodes of inverted OSCs ( Zhang et al, 2021 ), demonstrating the significance of nanocomposites towards enhancing the efficiency of devices. In similar studies, but with conventional OSCs based on MWCNTs ( Mugadza et al, 2017 ) and DWCNTs ( Zhang et al, 2018 ), as anodes, more stable devices with optimum PCEs of 0.68 and 1.71%, respectively, were fabricated.…”
Section: Transparent Conducting Electrodementioning
confidence: 99%
“…[ 81 ] The formation of oxide phases on Cu surface is detrimental to the electrical conductivity of the subsequent CuNW network. [ 82 ] To tackle these issues, a viable strategy is to adopt a composite of NWs with other nanomaterials such as conductive polymers (e.g., poly(3,4‐ethylenedioxythiophene) polystyrene sulfonate (PEDOT:PSS) or its variants), [ 83,84 ] metal oxides, [ 85,86 ] metals, [ 26,87,88 ] carbon nanotubes, [ 89–91 ] graphene, [ 81,92 ] or GO. [ 93,94 ] Furthermore, the incorporation of other nanomaterials into a metal‐based electrode can also offer considerable enhancement in other performance aspects such as enhanced electrode stretchability/conductivity, reduced surface roughness, [ 77,95–97 ] and corrosion protection for the adjacent layers in the cells.…”
Section: Metallic Nanomaterials For Flexible Transparent Electrodesmentioning
confidence: 99%